Pemberdayaan Siswa SMA Negeri 10 Seram Bagian Barat melalui Pelatihan Pembuatan Ecobrick sebagai Upaya Mengurangi Sampah Plastik di Negeri Kamarian - Ronald Darlly Hukubun; Laury Marcia Ch. Huwae; Helmalya Putri; Elsy Taruk Linggi; Adhe Fitri Rohly Elys; Josua Frans Trianto; Dhea Nurafni Firmansyah; Trisna Marsadi; Christiana Manuella Violynn; Chrisnata Manihuruk; Riskiya Riskiya; Merlin Getdha Putnarubun (Universitas Veteran Bangun Nusantara Sukoharjo, 2025)
A clean and healthy environment is very important for human development in Indonesia. Plastic waste, which is difficult to decompose, is the main problem faced by the community in Kamarian Village. In the community service activities carried out, there is a program for processing plastic waste into goods that have useful value, namely the ecobrick making program in the form of providing materials and direct training. The program for processing plastic waste into ecobricks was carried out at SMAN 10 Seram Bagian Barat, which succeeded in increasing students' knowledge significantly. The pretest results showed quite drastic improvements after the training, providing a positive impact on learning and environmental awareness. It is hoped that this program can be one of the keys to handling the waste problem in Kamarian Village.